Enhancing Student Engagement and Hydrosphere Literacy through Interactive Spatial Infographics in Geography Classrooms - Dzulqornain, Awib Muhtar; Sultoni, Achmad (CV Bumi Spasial, 2025)
The development of spatial-based infographics as an interactive learning medium was conducted based on several analyses, including material needs analysis, learner needs analysis, and analysis of previous research conducted by other scholars. The topic of hydrosphere dynamics, specifically rivers, is one of the subjects that requires learning media. This research and development aim to produce a geographical learning media in the form of spatial-based infographics as an interactive learning tool that is suitable for use in the hydrosphere dynamics topic on rivers. The development process was carried out until the media product met the criteria established by the researcher, which include interactivity, practicality, and informativeness. The research and development method used in this study follows the ADDIE model, with modified stages, namely: 1) analysis; 2) design; 3) development; and 4) evaluation. The data in this research and development consists of two types: qualitative and quantitative data. The product produced from this research and development is an interactive spatial-based infographic on the topic of rivers. Validation conducted by media and content experts indicated that the developed media is generally suitable for use in geography education, with a few recommendations for improvement. The evaluation results conducted by students on aspects of appearance, usage, content, and benefits, with 16 questions, yielded a percentage of 92.39%, meaning that the media is highly suitable and can be used as a learning tool in schools. Further recommendations for research and product development include the development of spatial-based infographics as an interactive learning media that can be operated on Android and iOS devices in the form of an app without using MS PowerPoint software.